2019
DOI: 10.1002/ps.5463
|View full text |Cite
|
Sign up to set email alerts
|

Novel 4‐pyrazole carboxamide derivatives containing flexible chain motif: design, synthesis and antifungal activity

Abstract: Background In recent years, carboxamide fungicides, targeting succinate dehydrogenase (SDH), have shown highly efficient and broad spectrum fungicidal activity. Structure–activity relationship (SAR) results for these commercial fungicides show that the carboxamide group was a key active group. This is useful information for the discovery of new pyrazole carboxamide derivatives with fungicidal activity. Results Twenty‐seven novel pyrazole carboxamides were designed and synthesized. Their fungicidal activities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 43 publications
0
77
0
Order By: Relevance
“…2,3 To date, 23 commercial SDHI fungicides have been approved for plant protection since the first launch of carboxin in 1966, and extensively applied to combat destructive plant fungi, such as Sclerotinia sclerotiorum, Rhizoctonia solani, and Botrytis cinerea. [4][5][6] In most of SDHI fungicides, the amide bonds are directly linked to the aromatic ring and polar moiety ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 To date, 23 commercial SDHI fungicides have been approved for plant protection since the first launch of carboxin in 1966, and extensively applied to combat destructive plant fungi, such as Sclerotinia sclerotiorum, Rhizoctonia solani, and Botrytis cinerea. [4][5][6] In most of SDHI fungicides, the amide bonds are directly linked to the aromatic ring and polar moiety ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazole is an important five‐membered heterocycle, which can be found in many drugs or pesticides . In the recent years, lots of succinate dehydrogenase inhibitors contain pyrazole motif , such as penthiopyrad, sedaxane, pydiflumetofen, bixafen, isopyrazam, and pyrapropoyne fluxapyroxad. Chemists are very interested in pyrazole because of its unique biological activity, such as antimicrobial , DPPH radical scavenging , anticancer , antifungal , anti‐inflammatory , nematicidal , and cholinesterases inhibitory activities.…”
Section: Introductionmentioning
confidence: 99%
“…Soybean, canola, cotton, corn, rice, and wheat were selected and underwent crop safety testing. [26][27][28][29] The commercial herbicide mesotrione was selected as a positive control. Of the tested crops, proximately 20 seeds (bud rate ≥ 85%) were sown in composite nutrient soil at a depth of 2 cm and grown at a temperature of 15 to 30°C in a glasshouse.…”
Section: Crop Selectivitymentioning
confidence: 99%
“…13 Studies over the past decades have provided important information on interactions between HPPD enzymes and HPPD inhibitors: 1,3-dicarbonyl and aromatic moieties are an indispensable pharmacophore for potent HPPD inhibition. Many researches [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] in HPPD inhibitors indicated that modification of the aromatic moieties is an effective way to get new derivatives with excellent weed control.…”
Section: Introductionmentioning
confidence: 99%